Viewing speech in action: speech articulation videos in the public domain that demonstrate the sounds of the International Phonetic Alphabet (IPA). Issue 3 (3rd July 2018) - Nakai, Satsuki; Beavan, David; Lawson, Eleanor; Leplâtre, Grégory; Scobbie, James M.; Stuart-Smith, Jane
ABSTRACT: In this article, we introduce recently released, publicly available resources, which allow users to watch videos of hidden articulators (e.g. the tongue) during the production of various types of sounds found in the world's languages. The articulation videos on these resources are linked to a clickable International Phonetic Alphabet chart ([International Phonetic Association. 1999. Handbook of the International Phonetic Association: A Guide to the Use of the International Phonetic Alphabet . Cambridge: Cambridge University Press]), so that the user can study the articulations of different types of speech sounds systematically. We discuss the utility of these resources for teaching the pronunciation of contrastive sounds in a foreign language that are absent in the learner's native language.